Factors that influence online repurchase intention among customers in Melaka Tengah / Nurfarrahain Abd Malik - Abd Malik, Nurfarrahain (Faculty of Business and Management, 2018)
People nowadays prefer to buy things online due to their busy schedule, thus online business has grow rapidly and lead to aggressive competition. It is important to identify the factors that may influence online repurchase intention because it may help the online businesses to grow. The aims of this study is to examine the relationship of perceived usefulness, ease of use, and trust on online repurchase intention. Cross-sectional method have been used in this study and for the sampling technique, the researcher select convenience sampling. Questionnaires were distributed to 300 respondent that consists of public in Melaka Tengah who used to repurchase product from the same online businesses. Multiple Regression Analysis have been used in order to statistically test the three proposed hypotheses. The researcher was found that the perceived usefulness, ease of use, and trust have a positive significant relationship with online repurchase intention. However, future research are recommended to increase the number of variables in their study, increase the sample size, or maybe targeting all group of ages in order to obtain a better results.